MODEL OF PLASTIC DEFORMATION OF POLYMER MATERIAL - SYNYUK, Oleg; KRAVCHUK, Olga; KRAVCHUK, Andrii; MAGDIN, Victor; ZOLOTENKO, Ivan (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article considers a model of plastic deformation of polymer material in the inter-roll space of the processing equipment under conditions of compression and shear, based on which it is established that the all-round pressure created in the polymer by the working bodies of the processing equipment causes only viscoelastic deformation, and therefore plastic compaction of the material in the process of its destruction does not occur.Numerical modeling of the plastic deformation of polymer waste between the rolls of the Relo profile made it possible to obtain the distribution of tangential stresses on the plane of the polymer material, based on which graphical dependences of the stress on the rate of deformation, which is determined by the circular speeds and radii of the rolls, are constructed.
Keywords: polymer material; stress-strain state; plastic; viscoelastic deformation; failure; stress; rolls